Assessment of phosphorus solubilization potential by Aspergillus terreus (Research, Society and Development, 2021)
Biosolubilization is one of the most innovative and promising technologies used in soil recovery, fully applicable to mining tailings, despite the immense incapacity of mining companies to achieve full use of their minerals, due to methods considered fallible in the mining process. This study envisioned the possibility of applying the solubilization of phosphorus present in iron ore tailings by Aspergillus terreus. The analytical tests proposed in the study indicated a maximum solubilization of 87.77% of the phosphorus by A. terreus from the iron ore tailings, corresponding to a concentration of 286.38 mg L-1 of soluble phosphorus, occurring within a period of 168 hours of biosolubilization process, and thus, contributing to an average solubilization of 1.70 mg h-1 of phosphorus by the fungal biomass. In addition, the microphotographic images obtained by SEM and TEM revealed, through analysis, the morphological and structural aspects of the mycelium and the cellular composition of the fungus, demonstrating the efficient solubilization of phosphorus by A. terreus. The information revealed by this study demonstrates the efficient solubilization of the phosphorus component present in the iron ore waste by the fungus, resulting in an excellent technology, and suggestive application in mining, as an alternative to reduce production costs, favoring the sustainability of the iron ore system. mining, and thus, contributing to a better quality of iron ore and a probable use of soluble phosphorus, for example, in the production of phosphate fertilizers.